Pengelolaan Supervisi Akademik Kepala sekolah Dasar Negeri 4 Grobogan - Astuti, Anastasia Tri, Prof. Dr. Sutama, M.Pd, Dr. Sabar Narimo, M.M., M.Pd (2016)
Anastasia Tri Astuti: Q 100140070 Management Supervision of Academic Affairs Head Elementary School 4 Grobogan. Sutama and Sabar Narimo. 69 pages. Thesis. Graduate program. Muhammadiyah University of Surakarta. 2016. The purpose of this study is to describe the planning of the academic supervision of State Elementary School Principal 4 Grobogan, to describe the implementation of the academic supervision of State Elementary School Principal 4 Grobogan, to describe the follow-up of the academic supervision of State Elementary School Principal 4 Grobogan. Types of Research in this study is a qualitative research design ethnography. The subject of research at the school, State Elementary School 4 Grobogan. Methods of data collection using interviews, observation, and documentation. Data analysis techniques to the analysis of flow starting from data collection, data reduction, data display, and verification / conclusions. Data validation was done by triangulation data. The results of this study were 1) Planning academic supervision at the State Elementary School 4 Grobogan carried out by the principal unit of time is based on the semester, each semester of at least one academic supervision. Planning academic supervision provide services and assistance to teachers in order to develop a learning situation conducted by the teacher in the classroom. Planning academic supervision performed by the principal will produce teaching conducted by the teacher to be effective; 2) Implementation of academic supervision by the head of State Elementary School 4 Grobogan done supervise the administration of teacher learning collective or group. Then adjusted to ongoing learning materials are taught by each teacher takes place every semester one. School principals are familiar approach in its delivery to the teachers so that the dialogue or communication two arah.3) Feedback public elementary school academic supervision 4 Grobogan carried out based on the implementation of the supervision of classroom visits by principals. Feedback academic supervision communicate the results to the teacher supervision as feedback to correct the mistakes made by the teacher. With the feedback the errors that arise over time will be lost and in the end the teacher may be professional in their duties Keywords: academic, implementation, management, supervision.